A better way to ….structure training in non-surgical aesthetics: An OMFS-led training scheme. Issue 1 (January 2022) - Olding, James; Fan, Kathleen
Abstract : Introduction: The recent All Party Parliamentary Group made 17 key recommendations regarding the non-surgical aesthetics (NSA) industry, including mandatory regulated training. Most training currently consists in unregulated, non-academically accredited one- or two-day courses. Lack of information around training has been highlighted as a key concern by doctors and dentists. Methods: We surveyed 90 medical and dental students regarding NSA, with questions about relevance to practice, understanding of training pathways, and regulation. We used these findings to create a non-profit mentorship scheme for soon-to-graduate and newly graduated medics and dentists, consisting in theoretical and practical components. The scheme leads mentees towards the OFQUAL-regulated, academically accredited Level 7 PG Diploma in Injectables. Results: Of 60 respondents, 85% were interested in practising NSA, and 92% thought it relevant to medical/dental practice, however only 15% had a good or very good idea of how to train. After one year of the scheme, we surveyed our mentees; 88% had a good or very good understanding of regulation, 90% for training pathways. The scheme now boasts 50 mentees, with teaching designed and delivered by a team of dual-qualified OMFS trainees. Conclusions: Complications from NSA treatments are widely reported. OMF Surgeons are uniquely placed to both manage complications, and to provide training in NSA. Robust training pathways are needed to address significant undergraduate and postgraduate interest in the area. Such pathways should lead to regulated and accredited courses, while ensuring doctors and dentists are given balanced and valid information in what is still a largely unregulated education sector.